Carbon Nanomaterials in Flames: from 0-D to 1-D and 2-D. Issue 19 (14th March 2016) - Luo, Chengzhi; Liao, Lingmin; Qi, Xiang; Liu, Yueli; Cao, Bing; Zhang, Jun; Zhang, Yupeng; Bao, Qiaoliang; Pan, Chunxu
ABSTRACT: Carbon nanomaterials are viewed as promising building blocks of future nanotechnology because of their superior electrical, thermal, and mechanical properties. Carbon nanomaterials can be synthesized by a variety of methods, in which flames offer a potential route in large quantities at a significantly lower cost. Our group has worked on growth of carbon nanomaterials involving carbon nanotubes (CNTs), carbon nanofibers (CNFs) and graphenes in flames for more than 15 years, and almost 100 journal papers have been published. In this paper, we review the advances in synthesis of carbon nanomaterials from flames in detail together with discussion on the major challenges and opportunities for practical applications.